Peroxymonosulfate Activation on a Hybrid Material of Conjugated PVC and TiO2 Nanotubes for Enhancing Degradation of Rhodamine B under Visible Light. (26th November 2020) - Ha, La Phan Phuong; Huy, Tran Hong; Huan, Pham Huu; Thu, Nguyen Thi Minh; Thi, Cao Minh; Van Viet, Pham
Abstract : Visible-light-driven photocatalysis is a robust technology for amending the negative effect of pollutants on the environment with a minimum energy use. Herein, we describe a simple approach to producing such a photocatalyst by coupling conjugated polyvinyl chloride (cPVC) with the TiO2 nanotube (TNT) thermolysis method. By activating peroxymonosulfate (PMS) to make a cPVC/TNT/PMS system using visible light as the source, we obtain a significant enhancement in the photocatalytic performance. We show that PMS use at a concentration of 3 mM can fully degrade rhodamine B (RhB) solution at a remarkably high concentration (200 mg L -1 ) just in 120 min under visible light. The cPVC/TNT/PMS system also shows excellent stability in recycling tests for at least five times. Further, by confining the active species in photocatalytic reactions, we report a thorough understanding of the extent of involvement from those radicals. Our work presents a robust approach to make a high-performance, visible-light-driven photocatalyst, which can be potentially used in practice.